Mathematical Modeling in Statistical Education contexts: a proposal for an activity aimed at Secondary Education (Research, Society and Development, 2022)
The work presented here comprises an innovative class in the Mathematics curricular component that proposes a study of Statistics through a teaching approach that has as its guiding principle the Mathematical Modeling. It aims to develop the numerical, analytical and critical treatment of statistical data from the information provided by the CoronavirusRN and RN+vaccine platforms. The study is guided by the following focal question: how to explore the information present in the CoronavirusRN and RN+Vaccine platforms from a Mathematical Modeling environment to teach Statistics through an innovative class. As a result, we present a didactic sequence composed of three moments, namely: experimentation (1), creation and resolution of a model (2), validation and modification of the model (3). The class prototype is aimed at 3rd year high school students.